2014
DOI: 10.1117/1.jbo.19.2.026010
|View full text |Cite
|
Sign up to set email alerts
|

Optimal optode montage on electroencephalography/functional near-infrared spectroscopy caps dedicated to study epileptic discharges

Abstract: Abstract. Functional near-infrared spectroscopy (fNIRS), acquired simultaneously with electroencephalography (EEG), allows the investigation of hemodynamic brain responses to epileptic activity. Because the presumed epileptogenic focus is patient-specific, an appropriate source/detector (SD) montage has to be reconfigured for each patient. The combination of EEG and fNIRS, however, entails several constraints on montages, and finding an optimal arrangement of optodes on the cap is an important issue. We presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 71 publications
0
55
0
Order By: Relevance
“…This would further open avenues for exploring optimal fusion montages with well‐placed and densely sampled electrodes and sensors to benefit from the fusion of the two modalities. Although, we addressed a similar issue in the context of near infrared spectroscopy (exploiting the forward model and defining some a prior target areas to place sensors in an optimal manner) (Machado, Marcotte, Lina, Kobayashi, & Grova, ), we believe that such an analysis was out of the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…This would further open avenues for exploring optimal fusion montages with well‐placed and densely sampled electrodes and sensors to benefit from the fusion of the two modalities. Although, we addressed a similar issue in the context of near infrared spectroscopy (exploiting the forward model and defining some a prior target areas to place sensors in an optimal manner) (Machado, Marcotte, Lina, Kobayashi, & Grova, ), we believe that such an analysis was out of the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach to generate the SD montage was recently proposed in Ref. 36, in which the authors aimed at maximizing the spatial sensitivity in one or several brain regions.…”
Section: Simultaneous Electroencephalography-functional Near-infraredmentioning
confidence: 99%
“…Serving the same purpose, data-based filtering techniques were also adapted into the analysis of long-term fNIRS data. 33 In addition, efforts have been made by Machado et al 36 to provide an optimal fNIRS emitter/detector montage in IED studies to maximize the sampling sensitivity over one or several brain regions. In summary, preliminary work confirms the clinical potential and usefulness of fNIRS: (1) it was seen as a robust tool to explore hemodynamics associated with seizures on adults, children, and neonates; (2) studies of seizures indicated a potential for epileptic focus localization; (3) it can possibly be used to study preictal hemodynamic changes; and (4) fNIRS hardware and software have steadily improved over the last few years and will most likely continue to improve, which may in turn benefit future clinical studies.…”
mentioning
confidence: 99%
“…When setting up an fNIRS experiment, optical sensors ('optodes') are placed on the scalp, which can be classified into sources (emitters) and detectors (receivers). Light emitted from a source is propagated through extracerebral and cerebral tissues up to a few centimeters, where some photons are scattered and absorbed before light reaches the detectors 5 . The spatial resolution of fNIRS is therefore in the range of 5-10mm 4 depending on the way source-detector pairs (or 'channels') are arranged on the scalp 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Light-sensitivity profiles are probabilistic models of photon absorption based on the tissues found between source and detector optodes 27 . Software packages, toolboxes and pipelines compute these profiles using Monte Carlo simulations to optimize optode layouts 1,5,[27][28][29][30] , thus promising an increase on signal quality and sensitivity for BCI applications. However, light sensitivity profile models require anatomical head data, either from an MRI-derived atlas or from subject-specific MRI data.…”
Section: Introductionmentioning
confidence: 99%